Effect of segregation on hot deformation behavior of GCr15 bearing steel in continuous casting - Mingyang Liu; Tianyu Zhang; Chenchong Wang; Ye Liu; Junyang Qian; Hongshuang Di; Qing Yin; Chi Zhang (Journal of Materials Research and Technology)
GCr15 steel, renowned as one of the most extensively utilized metallic materials in bearing applications, has been the subject of considerable research, particularly regarding its hot deformation behavior. However, the effect of macro- and micro-segregation on the hot deformation behavior of GCr15 steel remains underexplored. In this study, a comprehensive investigation was conducted to systematically assess the hot deformation behavior of continuously cast GCr15 steel under varying degrees of macro- and micro-segregation through hot compression testing. Flow curves were utilized to construct hot processing maps, enabling a detailed analysis of the effects of segregation on hot workability. The findings reveal that, at a deformation temperature of 800 °C and a strain rate of 10 s−1, the negatively segregated regions of GCr15 steel exhibit a greater propensity for instability during hot working than their positively segregated counterparts. This heightened instability, which accelerates with increasing true strain, can be attributed to stress concentrations arising from inhomogeneities inherent to the continuous casting process. Additionally, the negative macro-segregation zone demonstrated superior hot workability, attributed to its lower hardness. Based on these observations, the optimal hot processing conditions were identified as a deformation temperature of 1000 °C and a strain rate of 0.1 s−1.